Haida carved argillite pipes, Alaska, in engraving made 1839 - University of Washington Libraries
Photograph of engraving of two carved pipes made from argillite slate Caption on image: Slate pipes. -- Carving of the natives of North-West America Image from Edward Belcher's Narrative of a voyage round the world, 1843, v.1, p. 309